Hydrodynamic Characteristics and Pollutant Shifting Law of Shuangfengsi Reservoir under Flood Process - SUN Bolun; LIU Bin; ZHANG Yifan; XU Zhiheng; HAN Yuhang; CHANG Yifan (Renmin Zhujiang)
This paper aims to provide a theoretical basis for effective control of water pollution and technical support for joint simulation and control of reservoir hydrodynamic and water quality.It takes Shuangfengsi Reservoir as the research object and builds a hydrodynamic and water quality coupling model in virtue of MIKE21 to simulate the hydrodynamic characteristics and pollutant migration rule of a typical flood process in 1962.The output results show that in a typical flood process,the change of flow field in the reservoir area leads to drastic fluctuation of pollutant concentration.As the flood process progresses,the change curves of BOD and DO concentration are similar.Pollutant concentration drops rapidly at the initial stage of the flood,and when it drops to a certain value,the descending slope suddenly slows down until the end of the process.The change curves of NH4 and PO4 concentrations are similar.At the early stage of the flood,the concentrations at three points show an upward trend.As the point is further away from the storage location,the concentration increases faster and longer,and it rapidly decreases after rising to the highest point.The change curve of NO3 concentration is special.It shows a transient stable trend when the flood comes,and then increases abruptly to the maximum value of 2.5 mg/L and fluctuates up and down around it.The migration of pollutants in the reservoir area under the action of flood will change with the flood process.